IMPLEMENTATION SCIENTIFIC APPROACH IN THE COURSE OF HEALTH AND SAFETY STUDENTS IN MECHANICAL ENGINEERING EDUCATION STUDY PROGRAM FACULTY OF TEACHER TRAINING AND EDUCATION PALANGKA RAYA UNIVERSITY ACADEMIC YEAR 2015/2016 - Sri Murwantini; Jhonni Rentas Duling (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
With the implementation of the curriculum 2013 at primary and secondary education, student at the University of Palangka Raya especially mechanical engineering education Study Program as a candidate teachers are required to improve their knowledge and skills in order to implement the curriculum by using a scientific approach to learning. Step-by-step scientific approach to learning as intended includes observing, questioning, experimenting, associating and communicate. Researchers will discuss the problems is student response to the application of the scientific approach to the subjects Safety and Health at work. In this study, the data analysis performed inductively. Data obtained from observation sheets and questionnaires compiled systematically and then selected which are important and which will be studied and made a conclusion so easily understood by myself and others. The application of scientific approaches in learning the subjects Safety and Health at work greeted positively by the students by referring to high activeness in learning and positive response, (Agree/strongly Agree) are also high for its response to the application of this scientific approach.